Blood clots in COVID-19 patients: Simplifying the curious mystery. (January 2021) - Biswas, Sourav; Thakur, Vikram; Kaur, Parneet; Khan, Azhar; Kulshrestha, Saurabh; Kumar, Pradeep
Abstract: The universal phenomenon of blood clotting is well known to be protective in external cellular/ tissue injury. However, the emergence of unusual thrombotic presentations in COVID-19 patients is the real concern. Interaction of the spike glycoprotein with ACE2 receptor present in the host cell surface mediates the entry of SARS-CoV-2 causing COVID-19 infection. New clinical findings of SARS-CoV-2 pathogenesis are coming out every day, and one such mystery is the formation of mysterious blood clots in the various tissues and organs of COVID-19 patients, which needs critical attention. To address this issue, we hypothesis that, high ACE2 expression in the endothelium of blood vessels facilitates the high-affinity binding of SARS-CoV-2 using spike protein, causing infection and internal injury inside the vascular wall of blood vessels. This viral associated injury may directly/indirectly initiate activation of coagulation and clotting cascades forming internal blood clots. However, the presence of these clots is undesirable as they are responsible for thrombosis and need to be treated with anti-thrombotic intervention.